Managing the unknown : essays on environmental ignorance - Uekötter, Frank, 1970-; Lübken, Uwe (Environment in History: International Perspectives., 2014)
Information is crucial when it comes to the management of resources. But what if knowledge is incomplete, or biased, or otherwise deficient? How did people define patterns of proper use in the absence of cognitive certainty? Discussing this challenge for a diverse set of resources from fish to rubber, these essays show that deficient knowledge is a far more pervasive challenge in resource history than conventional readings suggest. Furthermore, environmental ignorance does not inevitably shrink with the march of scientific progress: these essays suggest more of a dialectical relationship be.